The Correlation between Social Support and Work-Family Enrichment with Psychological Well-Being among Married Nurses - Sony Wijaya (Universitas Muhammadiyah Yogyakarta, 2021)
Work and family are two domains where adults spend most of their time, and this can lead to role conflict. This study aimed to examine the correlation between social support and work-family enrichment with psychological well-being among married nurses. This research was quantitative study conducted through cross sectional design. The method used for data collection was questionnaires, including work-family enrichment, social support, and psychological well-being questionnaires. The sampling technique used was purposive sampling, with the inclusion criteria was married nurses who have children. The participants of this study were 100 nurses at Gibran Medika Utama healthcare. The statistical analysis was done by using regression test. The results obtained were: (1) there was a significant correlation between social support and work-family enrichment with psychological well-being (F = 26 036; p <0.05; R square = 0.214), (2) social support had a significant correlation with psychological well-being (r=0.252, p <0.05), and (3) work-family enrichment had a significant correlation with psychological well-being (r 0.219; p <0.05). Social support and work-family enrichment has significant correlation with psychological well-being, so it is suggested for the organization that it is necessary to conduct programs that consider work family balance. Further research is also suggested to involve other variables such as personality and life satisfaction.